Traumatic brain injury pharmacological treatment: recommendations - Renato Anghinah; Robson Luís Oliveira de Amorim; Wellingson Silva Paiva; Magali Taino Schmidt; Jéssica Natuline Ianof (Arquivos de Neuro-Psiquiatria)
ABSTRACT This article presents the recommendations on the pharmacological treatment employed in traumatic brain injury (TBI) at the outpatient clinic of the Cognitive Rehabilitation after TBI Service of the Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, Brazil. A systematic assessment of the consensus reached in other countries, and of articles on TBI available in the PUBMED and LILACS medical databases, was carried out. We offer recommendations of pharmacological treatments in patients after TBI with different symptoms.